An exploration into the quality of life of women treated for cervical cancer - Caroline Sabulei; Johanna E. Maree (Curationis, 2019)
Background: Cervical cancer mainly occurs among women from the developing world, and women face unique challenges in terms of their disease and treatment. Most women present with advanced cervical cancer and receive the standard curative treatment with external beam radiotherapy and brachytherapy with or without chemotherapy.